ANALISIS POTENSI KEBANGKRUTAN PADA PT. SEPATU BATA Tbk - Heriyanto, Rima Ratna Sari Elfreda Aplonia Lau, (EKONOMIA, 2020)
The purpose of this study is to find out the predictions of the potential occurrence of the first quarter 2018 bankruptcy at PT. Sepatu Bata Tbk, seen from financial statements, is measured by the Altman Z-score modification method with a problem resolution: Is PT. Sepatu Bata Tbk seen from the financial statements of the first quarter of 2018 measured by the indicated Altman Z-score modification potential to go bankrupt?The theoretical basis used in this study is financial management that focuses on the modified Altman Z-score method. Explains financial management is "All company activities related to businesses get company funds at a low cost as well as efforts to use and allocate these funds efficiently". The analysis tool used is the Altman Z-score Modification method predicting potential bankruptcy.The results showed that PT. Sepatu Bata Tbk is measured by the Altman Z-score modification method based on the calculation of the first quarter of 2018 resulting in a Z value of 6.84 greater than 2.60 meaning that it is not indicated that it has the potential to experience bankruptcy, the research hypothesis is accepted.